Potential Sources of the 1995 Venezuelan Equine Encephalitis Subtype IC Epidemic - Brault, Aaron C. (American Society for Microbiology, 2001)
Venezuelan equine encephalitis viruses (VEEV) belonging to subtype IC have caused three (1962–1964, 1992–1993 and 1995) major equine epizootics and epidemics. Previous sequence analyses of a portion of the envelope glycoprotein gene demonstrated a high degree of conservation among isolates from the 1962–1964 and the 1995 outbreaks, as well as a 1983 interepizootic mosquito isolate from Panaquire, Venezuela. However, unlike subtype IAB VEEV that were used to prepare inactivated vaccines that probably initiated several outbreaks, subtype IC viruses have not been used for vaccine production and their conservation cannot be explained in this way. To characterize further subtype IC VEEV conservation and to evaluate potential sources of the 1995 outbreak, we sequenced the complete genomes of three isolates from the 1962–1964 outbreak, the 1983 Panaquire interepizootic isolate, and two isolates from 1995. The sequence of the Panaquire isolate, and that of virus isolated from a mouse brain antigen prepared from subtype IC strain P676 and used in the same laboratory, suggested that the Panaquire isolate represents a laboratory contaminant. Some authentic epizootic IC strains isolated 32 years apart showed a greater degree of sequence identity than did isolates from the same (1962–1964 or 1995) outbreak. If these viruses were circulating and replicating between 1964 and 1995, their rate of sequence evolution was at least 10-fold lower than that estimated during outbreaks or that of closely related enzootic VEEV strains that circulate continuously. Current understanding of alphavirus evolution is inconsistent with this conservation. This subtype IC VEEV conservation, combined with phylogenetic relationships, suggests the possibility that the 1995 outbreak was initiated by a laboratory strain.